A jednak offline”: doniesienia z jakościowych badań nad hybrydyzacją samorzutnej aktywności poznawczej - Cichocki , Sylwester; Czysz , Robert; Przybyła , Tomasz; Klichowski , Michał (Studia Edukacyjne, 2020)
Background: In the contemporary culture we observed a kind of apology for the hybridization of cognitive activity. Nevertheless, we don’t know is it a real phenomenon or only a facade. To shed some new light on this issue, we investigated two qualitative studies on the hybridization of spontaneous cognitive activity. Methods: Three martial arts masters and four triathletes took part in these studies. A structured interview was used to collect data. Results: We found that professional and experienced athletes do not recognize a big potential for hybridization. They can’t imagine a strong hybridization of own, and their students, spontaneous cognitive activity, both in the current and the future technological reality. Conclusions: This study contradicts the idea of the superiority (in the cognitive contexts) of what online, over what offline.